Descriptors for Butia [Butia odorata (Barb. Rodr.) Noblick] - Bioversity International; Mistura, C.C.; Empresa Brasileira de Pesquisa Agropecuária; Barbieri, R.L.; Padulosi, S.; Alercia, A.; Marques Castro, C. (Bioversity International, 2015)
Descriptors for Butia were developed as part of the results of the PhD research project “Characterization of natural populations of Butia odorata in the Pampa Biome” (2013), and subsequent investigations on the diversity of Butia by the authors. It is the product of exhaustive collaboration amongst Embrapa Temperate Agriculture and Bioversity International, with consultations from Butia experts worldwide. The concept of crop descriptors has evolved over the years in response to changes in users’ needs. This is an attempt to combine a documentation system traditionally used in controlled environments (genebanks, breeding institutes) with an approach that involves people and their knowledge ‘in the field’. This descriptor list is an important resource for integrating both, biology and traditional knowledge in a standardized format. The Butia genus comprises 20 species which are distributed in Brazil, Uruguay, Paraguay and Argentina..B. odorata occurs in the grasslands of southern Brazil and Uruguay. Enhancement of conservation (ex situ and in situ) of Butia is instrumental to its sustainable use. In this regard, farmers and breeders must have access not only to a wide range of species, but also to the essential information about the traits that these species possess, which is highly strategic in promoting their utilization. Accurate characterization and evaluation data are therefore necessary, especially if these can be presented in a user-friendly and standardized Bioversity format such as the one followed through this descriptor list.